โลกาภิวัตน์ทางวัฒนธรรมกับการแพร่ขยายของวัฒนธรรมสมัยนิยมอเมริกัน : กรณีศึกษาเครือข่ายธุรกิจอาหารจานด่วนในประเทศบรูไนดารุสซาลาม - พิชญสุดา พลเสน (จุฬาลงกรณ์มหาวิทยาลัย, 2017)
Characterized by efficiency, "McDonaldization", explains global expansion of American fast food chains along with "Cultural Homogenization". Brunei Darussalam was chosen due to common perceptions as a ‘closed’ society, difficulty in breaking its boundaries as a non-secular Islamic state, with an powerful monarchical regime. The research methodology uses qualitative applications along with field work in Brunei to observe participant perception, conducting both a semi-structured interviews residents as a representative sample and a 31 questions survey of 100 locals within the same Brunei population. The findings reveal that 1.) McDonaldization as seen by the spread of fast food restaurants in Brunei, as in many other parts of the world, has not truly led to Cultural Homogenization, but rather, Cultural Pluralization. Brunei residents like American fast food as just another alternative. The American fast food chains engaged Bussiness Localization in adapting and pursuading resident satisfaction. 2.) Despite the success of McDonaldization other contradictory elements contribute to success in Brunei as well. For example, quick observations were made at McDonald’s in Bandar Seri Begawan, the capital city. Its "slow life" cultural attitude perpetuates a relaxed eating environment. Essentially, people are not in a hurry to eat quickly. People treat McDonalds as an ordinary restaurant, not a fast food outlet. It’s also has local menu items not found in other countries. 3.) Southeast Asian brands demonstrate better performance of McDonaldization than American brands as judged by the sample group who indicated greater satisfaction with taste, price, portion and location from local fast food chains. This phenomena characterizes local fast food chains as better suited for Brunei residents as well as utilizing "McDonaldization" and "Localization" processes better than the American fast food counterparts. 4.) Based on the interviews conducted, residents do not oppose American fast food. They don’t feel that eating its fast food imposes a foreign culture or cultural imperialism.